EVALUATION OF AGRICULTURE-BASED TOURISM PRODUCTS IN TINGGAN TRADITIONAL VILLAGE - Wayan Pantiyasa, I; Agus Sutiarso, Moh; Nyoman Arto Suprapto, I (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This study aims to determine the condition of tourism products in the tourist village of Pucak Tinggan, and to measure the level of tourist satisfaction with the service performance of the manager. Data collection methods used are observation, interviews, questionnaires and documentation. While the analytical method used is descriptive qualitative and measurement of CSI (Customer Satisfaction Index). From this research, it is known that tourism products in the tourist village of Pucak Tinggan are in the form of trekking packages visiting Pucak Mangu Temple, honey bee farming in the middle of a coffee plantation, biogas education, production of ground coffee and production of taro chips. The condition of supporting facilities along the trekking route such as gazebos, selfie spots and toilets has been damaged and is not well maintained due to cost constraints. Training and mentoring have been carried out by a team of IPBI lecturers targeting increasing management resources and supporting SME products based on agriculture. Service quality based on CSI (Customer Satisfaction Index) analysis is in the satisfactory category. This shows that tourists who are respondents in this study are satisfied with the performance of tourism managers in Pucak Tinggan tourism village.